PENGGUNAAN KONSEP RULES IN USE OSTROM DALAM ANALISIS PERATURAN PEMBENTUKAN ORGANISASI KESATUAN PENGELOLAAN HUTAN - Eno Suwarno; Hariadi Kartodihardjo; Lala M Kolopaking; Sudarsono Soedomo (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2015)
Following the establishment of Forest Management Units (KPHL/KPHP) by the Indonesian Ministry of Forestry, the next step that has to be done is the formation and operationalization of KPHL/KPHP organization by local governments. In reality, implementation of the respective obligation is stagnated due to a number of obstacles such as the regulatory aspects that haveless trust and difficult to be implemented by local governments. In the Institutional Analysis and Development (IAD Framework) from Elinor Ostrom, there is onecomponent, i.e. the rules-in-use concept that is possible to be applied as a tool to analyze the relationship between the content of a certain regulation and the structure of action-situation formed due to implementationof regulation.This study aimsto test effectiveness of the use of the concept of rules-in-use to find substantial shortcomings of the regulation on KPHL/KPHP formation at provincial level,as a basisforimprovement. Accordingly, analysis was performed on PP No.6/2007 jo. PPNo.3/2008, Permendagri No.61/2010 and PP No.41/2007by making analysis of regulation contents and feedback from the implementation process. Based on the results of this study, it can be concluded that the use of Ostrom's rules-in-use concept is adequately effective to find the shortcomings of KPHL/KPHP regulation content.